2009
DOI: 10.1089/gtmb.2008.0077
|View full text |Cite
|
Sign up to set email alerts
|

Screening of the DFNB3 Locus: Identification of Three Novel Mutations of MYO15A Associated with Hearing Loss and Further Suggestion for Two Distinctive Genes on This Locus

Abstract: Recessive mutations of MYO15A are associated with nonsyndromic hearing loss (HL) in humans (DFNB3) and in the shaker-2 mouse. Human MYO15A has 66 exons and encodes unconventional myosin XVA. Analysis of 77 Tunisian consanguineous families segregating recessive deafness revealed evidence of linkage to microsatellite markers for DFNB3 in four families. In two families, sequencing of MYO15A led to the identification of two novel homozygous mutations: a nonsense (c.4998C>A (p.C1666X) in exon 17 and a splice site m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…Five of the 11 genes we found mutated in this study have been reported in other families from Turkey, supporting our findings for their relatively high frequency in the Turkish population (Tekin et al, 2003(Tekin et al, , 2005Kalay et al, 2005Kalay et al, , 2007Wattenhofer et al, 2005;Ahmed et al, 2008). In addition, mutations in MYO15A, TMC1, and OTOF were reported with 5%, 3.4%, and 2.3% frequencies, respectively, in the deaf populations from Pakistan (Kitajiri et al, 2007;Nal et al, 2007;Choi et al, 2009), and mutations in MYO15A and TMC1 were found in 7.8% and 3.9%, respectively, of families without GJB2 mutations from Tunisia (Tlili et al, 2008;Belguith et al, 2009). Founder effects, heterozygote advantage, and assortative mating have all been proposed to explain the relatively high frequency of GJB2 (Gasparini et al, 2000;Nance et al, 2000;Van Laer et al, 2001;Meyer et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…Five of the 11 genes we found mutated in this study have been reported in other families from Turkey, supporting our findings for their relatively high frequency in the Turkish population (Tekin et al, 2003(Tekin et al, , 2005Kalay et al, 2005Kalay et al, , 2007Wattenhofer et al, 2005;Ahmed et al, 2008). In addition, mutations in MYO15A, TMC1, and OTOF were reported with 5%, 3.4%, and 2.3% frequencies, respectively, in the deaf populations from Pakistan (Kitajiri et al, 2007;Nal et al, 2007;Choi et al, 2009), and mutations in MYO15A and TMC1 were found in 7.8% and 3.9%, respectively, of families without GJB2 mutations from Tunisia (Tlili et al, 2008;Belguith et al, 2009). Founder effects, heterozygote advantage, and assortative mating have all been proposed to explain the relatively high frequency of GJB2 (Gasparini et al, 2000;Nance et al, 2000;Van Laer et al, 2001;Meyer et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…We may have missed some mutations even in the exons because our screening method was not 100% sensitive. An alternative explanation is the presence of yet another deafness gene at the DFNB3 locus, which has been previously suggested (Nal et al, 2007;Belguith et al, 2009;Shahin et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…31. PDZD7 was predicted to encode a protein smaller than harmonin or whirlin with only 2 PDZ domains.…”
Section: Pdzd7 Encodes a Ciliary Protein With Homology To The Ush1c Amentioning
confidence: 99%
“…Moreover, presence of p.L3160F MYO15A in a healthy control has been reported, and at least one additional deafness gene is predicted for the DFNB3 locus (31). Hence, p.L3160F MYO15A may be a benign variant, and a heterozygous mutation of an as yet unknown gene with cochlear and retinal function probably contributes to the Usher phenotype of U329-1 (digenic inheritance).…”
Section: Figurementioning
confidence: 99%